Global evaluative assessment of robotic skills in endoscopy (GEARS-E) : objective assessment tool for master and slave transluminal endoscopic robot - Takeshita, Nobuyoshi (2019)
Background and study aims: The Master and Slave Transluminal Endoscopic Robot (MASTER) is a novel robotic endosurgical system with two operating arms that offer multiple degrees of freedom. We developed a new assessment tool, the Global Evaluative Assessment of Robotic Skills in Endoscopy (GEARS-E), derived from existing tools in laparoscopic and robotic surgery, and evaluated its utility in the performance of procedures using MASTER. Methods: This was a pilot study conducted in vivo and ex vivo on animals. Three operators (Novice-1, Novice-2 and Expert) performed a total of five endoscopic submucosal dissections (ESD) using MASTER. Novice operators had no MASTER experience and the expert had previously performed eight MASTER ESDs. Operator performance was assessed by four independent evaluators using GEARS-E, which has a maximum score of 25 for five domains representing various skill-related variables (depth perception, bimanual dexterity, efficiency, tissue handling and autonomy). Results: The mean global rating scores for Novice-1 first attempt, Novice-1 second attempt, Novice-2 first attempt, Novice-2 second attempt and Expertʼs cases were 13.0, 16.0, 13.3, 15.5, and 21.5, respectively. The mean scores of each of the five domains were statistically higher for the second attempts compared to the first attempts for both Novice-1 and Novice-2. The mean scores of each of the five domains for the Expertʼs case were consistently higher than those for the two novice operators in both their first and second attempts. Conclusion: Results using GEARS-E showed correlations between surgical experience and MASTER ESD. As an assessment tool for evaluation of surgical skills, GEARS-E has great potential for application in MASTER procedures.